PROBLEMATIKA PENYELESAIAN PERSOALAN PEMILIHAN UMUM DI INDONESIA - Yaqub Cikusin (Media Keadilan: Jurnal Ilmu Hukum, 2022)
The 2019 general election will be held simultaneously to elect the legislature and executive. In its implementation, it is possible that significant election problems (both violations and disputes) arise. The reality is that the resolution of election problems is resolved in several institutions, namely Bawaslu, the State Administrative Court (PTUN), the District Court (PN), the Supreme Court (MA). Using a doctrinal type of research with a normative approach. Sources of legal material come from primary, tertiary and secondary legal materials, with analytical methods of prescriptive and descriptive analysis. The results of the study that, the settlement in several institutions leaves new problems because each institution has a different pattern and system of authority. Of course, it takes a lot of time to resolve election problems in several different institutions. it is like the schedule for holding elections which have been rigidly scheduled. This will disrupt the stages of the election process. In the end, justice will be difficult to obtain for justice seekers. So to provide justice in resolving election problems, election issues should be resolved in one (1) institution authorized to resolve election problems (both violations and disputes). The institution has a settlement system, namely within the institution it has 2 rooms, namely the violation and dispute room, each room has ad hoc judges a maximum of 5 people (from academics, election officials/activists and taken from career judges), the nature of the final and appeal decisions. The settlement system has the principle of fast, easy and cheap.Keywords: election problems; settlement institutions; ineffective. ABSTRAKPelaksanaan pemilu 2019 dilakukan secara serentak untuk memilih legislatif dan eksekutif. Pada pelaksanaanya tidak menutup kemungkinan muncul persoalan (baik pelanggaran dan sengketa) pemilu yang signifikan. Realitanya penyelesaian persoalan pemilu diselesaikan dibeberapa lembaga yaitu Bawaslu, pengadilan Tata Usaha Negara (PTUN),Pengadilan Negeri (PN), Mahkamah Agung (MA). Menggunakan jenis penelitian doctrinal dengan pendekatan normatif. Sumber bahan hukum berasal dari bahan hukum primer, tersier dan sekunder, dengan metode analisis preskriptif dan deskriptif analitik. Hasil penelitian bahwa, Penyelesaian di beberapa lembaga ini meninggalkan persoalan baru karena setiap lembaga memiliki pola dan sistem kewenangan yang berbeda beda, Tentunya diperlukan waktu yang tidak sedikit dalam menyelesaikan persoalan pemilu di beberapa lembaga yang berbeda. Tak ubahnya jadwal pelaksanaan pemilu yang telah terjadwal secara rigid. Hal ini akan menganggu tahapan pelaksanaan pemilu. Pada akhirnya keadilan akan sulit didapat oleh pencari keadilan. Maka untuk memberikan keadilan dalam menyelesaikan persoalan pemilu semestinya persolaan pemilu diselesaikan di satu (1) lembaga yang berwenang untuk menyelesaikan persoalan pemilu (baik pelanggaran maupun sengketa). Lembaga tersebut memiliki sistem penyelesaianya yaitu di dalam lembaga memiliki 2 kamar yaitu kamar pelanggaran dan sengketa,  setiap kamar memiliki hakim ad hoc maksimal 5 orang (dari akademisi, pegiat pemilu/aktivis serta diambil dari hakim karier), sifat putusan final dan banding. Sistem penyelesaian memiliki asas cepat, mudah dan murah.